Social Network Analysis untuk Pemeringkatan Popularitas Makanan Cepat Saji Menggunakan Metode PSI - Wibisono, Setyawan; Hadikurniawati, Wiwien; Lestariningsih, Endang; Wahyudi, Eko Nur; Cahyono, Taufiq Dwi (Jurnal Teknik Informatika UNIKA Santo Thomas, 2024)
This research aims to rank the popularity of fast-food brands in Indonesia based on Twitter conversations using the Preference Selection Index (PSI) method and validate the results with COPRAS and AHP-COPRAS methods. Data were obtained by crawling Twitter from April 21, 2023, to April 28, 2023. Seven well-known brands, such as KFC, MCD, PizzaHut, Hokben, Solaria, JCo, and Richeese, were evaluated as alternatives using eight criteria through Social Network Analysis. The criteria were categorized into advantageous and disadvantageous, and preference values were calculated using PSI. After normalizing the decision matrix, calculations were performed for preference variation and overall preference values. Alternatives were ranked based on the preference selection index, and the results were validated with COPRAS and AHP-COPRAS. The results revealed significant differences in rankings between the PSI method and others. The alternative that received the highest rank changed from A2 (COPRAS and AHP-COPRAS) to A3 (PSI). This emphasizes the importance of choosing the right method for brand ranking, as it can influence decision-making. Method validation through result comparison with other methods provides additional insights into the reliability of the PSI method in the context of this research.